1969
DOI: 10.1001/archneur.1969.00480160015001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Parkinsonism With Levodopa

Abstract: Some turn this sickness yet might take, Even yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
216
1
6

Year Published

1970
1970
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(234 citation statements)
references
References 16 publications
7
216
1
6
Order By: Relevance
“…Few cases of acute overdose with levodopa or levodopa conjugated with carbidopa have been reported (1)(2)(3), though levodopa has been used for more than 35 years in the treatment of Parkinson's disease (4)(5)(6). This is the first report of an acute overdose of a controlled-release formulation of levodopa with serial measurements of dopamine, adrenalin and noradrenalin plasma concentrations.…”
Section: Introductionmentioning
confidence: 92%
“…Few cases of acute overdose with levodopa or levodopa conjugated with carbidopa have been reported (1)(2)(3), though levodopa has been used for more than 35 years in the treatment of Parkinson's disease (4)(5)(6). This is the first report of an acute overdose of a controlled-release formulation of levodopa with serial measurements of dopamine, adrenalin and noradrenalin plasma concentrations.…”
Section: Introductionmentioning
confidence: 92%
“…Subsequent open-label levodopa trials with oral preparations confirmed both short and longterm benefits, and a double-blind placebo controlled trial followed (Barbeau 1969;Cotzias et al 1969;Yahr et al 1969). These reports launched levodopa's establishment as the premier agent to treat Parkinson's disease symptoms and signs.…”
Section: Levodopa and Dopamine-based Therapiesmentioning
confidence: 99%
“…The plasma half-life of levodopa in the carbidopa-levodopa immediate-release formulation is approximately 90 min [13], while all oral dopamine agonists have half-lives greater than 6 h [11]. Laboratory studies in MPTP-lesioned primate models of PD have consistently shown that development of dyskinesia phenotypes is closely linked to intermittent levodopa administration (relative to dopamine agonists); and that once present, such dyskinesias are significantly reduced by switching from levodopa to dopamine agonists [14][15][16][17][18].…”
Section: Cds and The Transition To Cddmentioning
confidence: 99%